Taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae) - Perkins, Philip D. (Zootaxa, 2020)
The taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 is presented. The known fauna now consists of 12 species, six of which are described as new species. The new species are diagnosed, and high-resolution images of the habitus and male genitalia of each species are given. The following new species are described: H. armatus n. sp., H. hamulus n. sp., latipennis n. sp., H. lobissimus n. sp., H. maximus n. sp., and H. simplicatus n. sp. Habitus and male genitalia illustrations are also presented for H. choennii Makhan 1992, and H. hellmani Perkins 2019. New locality data are provided for H. argutus Knisch 1921, H. bicarinatus Perkins 2019, H. bituberculatus Perkins 2019, H. choennii Makhan 1992, H. hellmani Perkins 2019, and H. piroei Makhan 1992.